2014
DOI: 10.1007/s00221-014-4096-5
|View full text |Cite
|
Sign up to set email alerts
|

Insular infarct size but not levosimendan influenced myocardial injury triggered by cerebral ischemia in rats

Abstract: Cerebral injuries can trigger stress-related cardiomyopathy. The extent of cerebral injury and the involvement of the insular cortex influence the incidence and extent of myocardial injury (MI), and drugs with proven neuroprotective and cardioprotective properties such as levosimendan might be beneficial. This hypothesis was addressed in a rat model of transient middle cerebral artery occlusion. Transient brain ischemia was induced for 60 min by intraluminal occlusion of the middle cerebral artery in 40 male W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The mice with cardiac dysfunction had more severe insular cortex damage and increased sympathetic activity [75]. Moreover, larger insular infarct volumes correlate with more severe myocardial injury [87]. Meanwhile, this evidence supports the notion that the lateralization of the insula is closely connected with autonomic responses.…”
Section: Central Autonomic Network Dysregulation and Hypothalamic-pit...supporting
confidence: 65%
“…The mice with cardiac dysfunction had more severe insular cortex damage and increased sympathetic activity [75]. Moreover, larger insular infarct volumes correlate with more severe myocardial injury [87]. Meanwhile, this evidence supports the notion that the lateralization of the insula is closely connected with autonomic responses.…”
Section: Central Autonomic Network Dysregulation and Hypothalamic-pit...supporting
confidence: 65%
“…Moreover, a recent report showed that levosimendan was beneficial in a model of injury to the immature brain following cardiopulmonary bypass (Namachivayam et al, 2014). Finally, Varvarousi et al (2014) described positive effects of levosimendan in post-cardiac arrest brain injury, and Bleilevens et al (2014) showed that levosimendan treatment significantly reduces cerebral infarct size in the cortex in a rat model.…”
Section: Discussionmentioning
confidence: 94%
“…32 The major pathophysiological aspect of altered function within the brainheart axis in the pathogenesis of stroke-associated NSC is fur-ther supported by experimental and clinical research evidence which indicates a correlation between the development of cardiac dysfunction and ischemic events involving the insular cortex, especially the right insular cortex. [33][34][35] Indeed, current neuroimaging studies using functional magnetic resonance and positron emission tomography have confirmed the insular cortex as a cardinal regulator of the central autonomic nervous system. 36 The latter observation is crucial if taken into account that blood supply of insular cortex comes from the middle cerebral artery making it particularly susceptible to cerebrovascular disease.…”
Section: Pathophysiology Of Cardiac Dysfunction In Strokementioning
confidence: 99%
“…Moreover, supra-physiological levels of epinephrine may have a negative inotropic effect, as they contribute to the switching of β 2 -adrenergic receptors from canonical stimulatory G-protein-activated cardiostimulant to inhibitory G-protein-activated cardiodepressant pathways [ 32 ]. The major pathophysiological aspect of altered function within the brain-heart axis in the pathogenesis of stroke-associated NSC is further supported by experimental and clinical research evidence which indicates a correlation between the development of cardiac dysfunction and ischemic events involving the insular cortex, especially the right insular cortex [ 33 - 35 ]. Indeed, current neuroimaging studies using functional magnetic resonance and positron emission tomography have confirmed the insular cortex as a cardinal regulator of the central autonomic nervous system [ 36 ].…”
Section: Nsc In Patients With Strokementioning
confidence: 99%